TEKNOLOGI MEMBRAN MIKROFILTRASI (MF) UNTUK PEMURNIAN TOTAL NITROGEN DARI SAMPAH CAIR (LEACHATE) DI TPA WANCI MEKAR KERAWANG - Nurhayati; Yadi Supriyadi (Fakultas Teknik - Universitas Satya Negara Indonesia, 2024)
Waste processing is currently being at the level of the government, especially solid waste, while liquid waste (leachate) has not been widely processed. Liquid waste is very disturbing to the environment because of the odor from the decomposition process of microorganisms and a little photolysis process. Leachate will cause the environmental carrying capacity to exceed and the impact of this leachate will continue because the community around the TPA location will use the river water that passes through the area to irrigate rice fields and other plants. Thus, it is necessary to conduct research on liquid waste (leachate) that is dumped into water areas, especially into rice fields, which can be used as liquid fertilizer after knowing the characteristics of the organic content in it using membrane technology. Leachate that has been centrifuged enters the feed tank and is then given a pressure of 1.2.3 Bar and a filter time of 15, 30, and 45 minutes. The results obtained are the performance of the Microfilter membrane so that the leachate flux is high, namely at a pressure of 2 bar with a time of 15 minutes, a flux value of 286 l / m2, hour will be obtained. The highest concentration of total nitrogen value was obtained at a pressure of 1 bar with a time of 15 minutes, which was 1920.800 mg/l. Based on the analysis of diversity on the total nitrogen value, it was obtained that the F count for the pressure factor was 1384.149 and the F count from the Time factor was 1231.843, when compared with the F value from the F distribution list (F table) it turned out that both were very significant as well as seen in the interaction